Ward Based X-Ray Facilities Can Improve Services - Heymann, T D (J R Coll Physicians Lond, 1996)
As part of a wider experiment, a satellite X-ray facility, run by 2 part-time radiographers (1 whole time equivalent), was established to provide all plain radiographs on inpatients in a patient focused unit of 114 beds created from 4 medical wards of a 370-bed district general hospital providing acute services to a local population of about 200,000. Fewer staff were needed to provide an X-ray and report on the ward, the number of steps was reduced from 54 to 42 and the time taken from 104 to 62 minutes. Radiographers spent a smaller proportion of their time on professional duties but freed up substantial time for other members of staff. The reactions of all involved, staff and patients, were favourable. With present technology, the patient focused approach brings net benefits and possibly decreases costs, but the balance may swing back to centralisation when picture archiving and communication systems (PACS) become more widely available.